Salivary biomarkers and training load during training and competition in paralympic swimmers - Sinnott-O`Connor, C.; Comyns, T. M.; Nevill, A. M.; Warrington, G. D. (International Journal of Sports Physiology and Performance, 2018)
Context: Stress responses in athletes can be attributed to training and competition, where increased physiological and psychological stress may negatively affect performance and recovery. Purpose: To examine the relationship between training load (TL) and salivary biomarkers immunoglobulin A (IgA), alpha-amylase (AA), and cortisol across a 16-wk preparation phase and 10-d competition phase in Paralympic swimmers. Methods: Four Paralympic swimmers provided biweekly saliva samples during 3 training phases—(1) normal training, (2) intensified training, and (3) taper—as well as daily saliva samples in the 10-d Paralympic competition (2016 Paralympic Games). TL was measured using session rating of perceived exertion. Results: Multilevel analysis identified a significant increase in salivary immunoglobulin A (sIgA: 94.98 [27.69] µg/mL), salivary alpha-amylase (sAA: 45.78 [19.07] µg/mL), and salivary cortisol (7.92 [2.17] nM) during intensified training concurrent with a 38.3% increase in TL. During the taper phase, a 49.5% decrease in TL from the intensified training phase resulted in a decrease in sIgA, sAA, and salivary cortisol; however, all 3 remained higher than baseline levels. A further significant increase was observed during competition in sIgA (168.69 [24.19] µg/mL), sAA (35.86 [16.67] µg/mL), and salivary cortisol (10.49 [1.89] nM) despite a continued decrease (77.8%) in TL from the taper phase. Conclusions: Results demonstrate that performance in major competition such as Paralympic games, despite a noticeable reduction in TL, induces a stress response in athletes. Because of the elevated stress response observed, modifications to individual postrace recovery protocols may be required to enable athletes to maximize performance across all 10 d of competition.